The Vaccine Trust Framework: mixed-method development of a tool for understanding and quantifying trust in health systems and vaccines - Muhula PhD, S O; Osur PhD, J; et al... (Elsevier Ltd, 2025)
Summary
Trust is a key component of vaccine demand; however, there is no consensus on how to define trust and a lack of actionable, contextually grounded measurement tools validated in low-income and middle-income countries.
Aim
To develop and validate a Vaccine Trust Framework and a trust measurement tool that can be used to leverage trust to drive resilient vaccine demand.
Methods
An exploratory sequential mixed-methods study was conducted.
Ethnographic research in Nigeria, Kenya, and Pakistan to define trust in the context of childhood, HPV, and COVID-19 vaccines.
Validation through a nationally representative survey of caregivers of adolescents in Kenya and Pakistan.
Psychometric assessment using confirmatory factor analysis and logistic regression.
Findings
The Vaccine Trust Framework consists of four interlinked domains and 15 measurable dimensions:
Health system promise, health system delivery, vaccine promise, and vaccine delivery.
Survey data were collected from 3670 participants in Kenya and 3734 participants in Pakistan.
Trust influenced vaccine behaviour and intentions, supported by associations between quantitative trust scores and vaccination status.
Regional variation in trust was observed within Kenya and Pakistan, aligning with qualitative perceptions of local vaccine and health systems.
Interpretation
The Vaccine Trust Framework provides a validated and contextually grounded tool for assessing trust in health systems and vaccines in low-income and middle-income countries.
It can be used as a:
Prognostic tool to anticipate vaccine demand
Intervention design aid to support trust-building strategies
Trust measurement tool within intervention or monitoring studies
Further research is ongoing to assess its utility in designing and measuring the impact of trust-building interventions.
Keywords: Vaccine